2015
DOI: 10.1111/cea.12498
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus induces indoleamine 2,3‐dioxygenase activity: a potential novel role in the development of allergic disease

Abstract: Our data show for the first time that RSV can induce the expression and bioactivity of IDO in human moDC, in a virus replication-dependant fashion. We suggest that RSV activation of IDO could be a potential mechanism for the development of allergic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 89 publications
3
26
2
Order By: Relevance
“…Similar to our findings with lung epithelial A549 cells, in neuronal cells IFN-␥ strongly induced IDO expression, causing inhibition of HSV replication, which could be rescued by Trp (54). Interaction of IDO with several other viruses, such as HIV, cytomegalovirus, RSV, hepatitis virus, and influenza A virus, has been unraveled recently, but mainly in the context of T cell responses and induced immunity (52,(55)(56)(57)(58). The effect of IDO on PIV3, however, was appreciated in nonimmune cells; it is thus representative of a cellintrinsic mechanism that directly inhibits viral gene expression.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to our findings with lung epithelial A549 cells, in neuronal cells IFN-␥ strongly induced IDO expression, causing inhibition of HSV replication, which could be rescued by Trp (54). Interaction of IDO with several other viruses, such as HIV, cytomegalovirus, RSV, hepatitis virus, and influenza A virus, has been unraveled recently, but mainly in the context of T cell responses and induced immunity (52,(55)(56)(57)(58). The effect of IDO on PIV3, however, was appreciated in nonimmune cells; it is thus representative of a cellintrinsic mechanism that directly inhibits viral gene expression.…”
Section: Discussionsupporting
confidence: 86%
“…IDO is distributed mainly in dendritic cells and certain tumour cells. It has also been demonstrated that IDO is significantly increased in certain viral pathophysiological conditions . Although few IDO + cells were found in normal skin epithelium, they were abundantly expressed in wart tissue.…”
Section: Discussionmentioning
confidence: 98%
“…It has also been demonstrated that IDO is significantly increased in certain viral pathophysiological conditions. 27,28 Although few IDO + cells were found in normal skin epithelium, they were abundantly expressed in wart tissue. It is interesting that the wart IDO was derived mainly from the epidermal cells of the warts rather than the LCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports show that RSV induces Indoleamine-2,3-dioxygenase (IDO) in dendritic cells (DCs) [11] and Mesenchymal Stromal Cells (MSCs) [12] and there is a direct correlation between RSV replication and IDO expression [11]. Since IDO is an immunomodulatory enzyme that has been shown to affect a number of immune responses including some linked to RSV [11,12], it might participate in the pathogenesis of RSV disease. IDO catalyzes the degradation of the essential amino acid L-tryptophan and generates a family of catabolites known as kynurenines.…”
Section: Introductionmentioning
confidence: 99%